2018
DOI: 10.1016/j.rmcr.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Transformation to small cell lung cancer after first-line afatinib treatment

Abstract: Acquiring resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) is inevitable. Transformation to small cell lung cancer (SCLC) is reported as a possible mechanism of this acquired resistance. We describe the case of a 35-year-old man with lung adenocarcinoma harboring EGFR exon 19 deletion. After 7 months of successful treatment with afatinib, he experienced relapse and rebiopsy revealed SCLC with EGFR exon 19 deletion. Tumor marker tests at this point showed normal levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Chemotherapy might transform a SCLC to adenocarcinoma with T790M expression, but also, osimertinib might transform an adenocarcinoma with T790M expression to SCLC 15,17. There are also cases where afatinib administration transformed adenocarcinoma to SCLC18 and both SCLC and squamous cell carcinoma 19. Moreover, it has been observed that ALK-positive patients might transform to SCLC 20.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy might transform a SCLC to adenocarcinoma with T790M expression, but also, osimertinib might transform an adenocarcinoma with T790M expression to SCLC 15,17. There are also cases where afatinib administration transformed adenocarcinoma to SCLC18 and both SCLC and squamous cell carcinoma 19. Moreover, it has been observed that ALK-positive patients might transform to SCLC 20.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, transformation of NSCLC into SCLC is hypothesized as a possible mechanism of acquired resistance to EGFR-TKIs [11,50]. After SCLC transformation, the EGFR mutation is retained, EGFR protein decreases, and patients show limited response to EGFR-TKIs [51].…”
Section: Egfr-independent Resistance Mechanismsmentioning
confidence: 99%
“…The first report described a case of a lung adenocarcinoma harboring EGFR exon 19 deletion that, after seven months of treatment with afatinib, progressed and showed SCLC transformation at re-biopsy with concomitant EGFR exon 19 deletion. Afatinib was discontinued and chemotherapy was administered with a cisplatin and irinotecan regimen, with no disease progression after four cycles of chemotherapy [95]. Similarly, the second case report described a switch of tumor histotype to SCLC with features of a G3 neuroendocrine carcinoma and positivity for exon 19 deletion of EGFR .…”
Section: Mechanisms Of Resistance To Tkis In Egfrmut Nsclc and Trementioning
confidence: 99%